Isoliensinine: A Natural Compound with “Drug-Like” Potential - Cheng, Yan; Li, Hong-Li; Zhou, Zi-Wei; Long, Hui-Zhi; Luo, Hong-Yu; Wen, Dan-Dan; Cheng, Lin; Gao, Li-Chen (Frontiers in Pharmacology, 2021)
Isoliensinine, a bisbenzylisoquinoline alkaloid isolated from Nelumbo nucifera Gaertn, exerts a variety of beneficial effects, such as antitumor, cardioprotective, antioxidant, antidepressant, and anti-HIV effects, and ameliorates T2DM with hyperlipidemia and Alzheimer’s disease. In this paper, the recent literature on isoliensinine, including its pharmacology, pharmacokinetics, synthesis and extraction, is summarized. Moreover, possible future prospects and research directions are also discussed. Studies on isoliensinine were found by searching a combination of keywords including “pharmacology”, “pharmacokinetics”, and “synthesis and extraction” in the main databases, including PubMed, Google Scholar, Web of Science, NCBI, and Wan Fang. Many studies have pointed out that a major limitation of isoliensinine is its poor solubility in aqueous media. Considering its advantages and limitations, isoliensinine can be used as a lead compound to develop novel efficient and low-toxicity derivatives. The available literature indicates that isoliensinine displays “drug-like” potential. Additionally, there are many related issues and novel mechanisms that need to be explored.